Necessidades e uso de informação na prática dos professores de ciências. - Oliveira, Glicia Lany Couto de (2013)
The use of information is an indispensable practice to any individual and as such, it is also essential to the professionals of education, especially teachers. Hence the importance of the issue here exposed being made clear by the fact of these professionals need of information for the development of their teaching practices. The present research on "Needs and use of information in the practice of science teachers" aims to analyze the needs and use of information of teachers from the urban area of the municipality of Santa Rita - PB. In that sense, the following question arises: What are the needs and use of information for science teachers in their teaching practices? An alternative approach of the Users´ Studies was used in this research, and the Sense-Making model was prioritized for offering through universal categories of cognitive metaphor, the situation (need for information), gap (cognitive emptiness), and use (informational help to bridge the cognitive emptiness), the logical way for meeting the research objectives. This is a descriptive field research, with a propositional nature. The population is consisted of 28 science teachers, distributed in schools in the urban areas of the municipality of Santa Rita. As an instrument of data collection, the mixed questionnaire was used. Data analysis, of qualitative and quantitative basis, shows that the study group is composed of qualified teachers who prioritize the post-graduation demonstrating interest in being updated for the practice of teaching. Although acknowledging the difficulties of the profession, most teachers manifest satisfaction and teach for pleasure in self-fulfillment. With emphasis on the categories of the Sense-Making, situation-gap-use, the situation reveals that teachers are constantly seeking to meet their information needs through the Internet, books, and educational videos, among others. In the gaps, barriers of time, language, terminology and quality of information were the most displayed, but they developed strategies that minimized the difficulties and could make use of the information. The use of information was centered on the development of teaching activities and the teachers were satisfied with it because it solved their informational problem. Actions to contribute to a better performance of the studied teachers about those questions in their teaching and pedagogical practices were proposed. We conclude that the development of the research contributed to the basis of the Science of Information, which is to provide information and impart knowledge to those who need it, making this the social responsibility in this area of knowledge, as well as in Education, when it makes itself responsible for the challenge of educating a society. Studying the teachers´ information needs and how they guide the search process and the use of information to satisfy their informational needs towards teaching practice, was assigned as a process of great value.